The economics of dryland management - Dixon, John. (London Earthscan Publications, 1989)
We have always had land in which the agricultural productivity is limited because there is not enough moisture. Systems of farming and burning often degrade dryland further until it is desert. Today, however, the problem is becoming much more serious. Over 20 per cent of the world's population lives in dryland areas, and unless action is taken drylands will increase dramatically. This book focuses on the people who live and .farm in the drylands, their use of land resources and the economic returns from their decisions. In a clear and thorough economic appraisal, the authors show how it is still possible to arrest the problem. Originally published in 1989
Includes index
Keywords: Arid region